CHEMICAL COMPOSITION OF THE ESSENTIAL OIL OF ALOYSIA TRIPHYLLA "CEDRON" AS INPUT FOR THE PREPARATION OF A MOUTHWASH - Huerta León, Jenny Rosalyn (2021)
Objectives: to determine the antimicrobial activity of the essential oil obtained from the leaves and stems of Aloysia triphylla “Cedrón” from the city of Huaraz, department of Ancash, district of Mancos. Materials and methods: The method of hydrodistillation by dragging of Steam to obtain the essential oil and for the determination of the antibacterial activity was carried out by the agar diffusion methodology against Streptococcus mutans ATCC 25175 and Porphyromonas gingivalis ATCC 33277, comparing them with a positive control which was a commercial chlorhexidine mouthwash at 0.05%. Results: a yield of 0.11 was obtained and in the microbiological study, 21.3 mm halos of the essential oil and 19.9 mm of the positive control against Streptococcus mutans ATCC 25175 and 35.5 mm in the essential oil were obtained. and 25.4 mm of the positive control against Porphyromonas gingivalis ATCC 33277. Conclusions: It is concluded that the antimicrobial activity demonstrated by the essential oil of Aloysia triphylla (lemon verbena) is superior to the positive control that was a commercial oral chlorhexidine rinse at 0.05%, and this can be used as a source in the preparation of pharmaceutical preparations in the treatment of infections caused by these microorganisms